Deep‐Red Perovskite Light‐Emitting Diodes Based on One‐Step‐Formed γ‐CsPbI3 Cuboid Crystallites. Issue 51 (10th October 2021) - Miao, Yanfeng; Liu, Xiaomin; Chen, Yuetian; Zhang, Taiyang; Wang, Tianfu; Zhao, Yixin
Abstract: Inorganic CsPbI3 perovskite with high chemical stability is attractive for efficient deep‐red perovskite light‐emitting diodes (PeLEDs) with high color purity. Compared to PeLEDs based on ex‐situ‐synthesized CsPbI3 nanocrystals/quantum dots suffering from low conductivity and efficiency droop under high current densities, in situ deposited 3D CsPbI3 films from precursor solutions can maintain high conductivity but show high trap density. Here, it is demonstrated that introducing diammonium iodide can increase the size of colloids in the precursor solution, retard the phase‐transition rate, and passivate trap states of the in‐situ‐formed cuboid crystallites. The PeLED based on the one‐step‐formed 3D CsPbI3 cuboid crystallite films shows a peak external quantum efficiency (EQE) value up to 15.03% because of the high conductivity and reduced trap states. Furthermore, this one‐step method also has a wide processing window, which is attractive for flow‐line production of large‐area PeLED modules. The fabrication of a 9 cm 2 PeLED that exhibits a peak EQE of 10.30% is successfully demonstrated. Abstract : A facile one‐step method to in situ deposit γ‐phase 3D CsPbI3 films consisting of cuboid crystallites is achieved by introducing 1, 3‐propanediamine dihydriodide (PDAI). The PDAI–perovskite light‐emitting diode (PeLED) can reach a record efficiency of 15.03% for 3D CsPbI3 PeLEDs and a peak efficiency of 10.30% of a 9 cm 2 PeLED.